2002
DOI: 10.1172/jci13462
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl peptidase I activates neutrophil-derived serine proteases and regulates the development of acute experimental arthritis

Abstract: Leukocyte recruitment in inflammation is critical for host defense, but excessive accumulation of inflammatory cells can lead to tissue damage. Neutrophil-derived serine proteases (cathepsin G [CG], neutrophil elastase [NE], and proteinase 3 [PR3]) are expressed specifically in mature neutrophils and are thought to play an important role in inflammation. To investigate the role of these proteases in inflammation, we generated a mouse deficient in dipeptidyl peptidase I (DPPI) and established that DPPI is requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
125
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(132 citation statements)
references
References 41 publications
7
125
0
Order By: Relevance
“…In addition, macrophage maturation, migratory capacity, cytokine gene expression and phagocytosis are affected by SGD in both humans and mice [14,15]. In the case of dipeptidyl peptidase I (DPPI) deficiency, which results in a loss of function of the PMN serine proteases elastase, cathepsin G and proteinase-3 [16], a secondary macrophage dysfunction is also observed [17][18][19]. PMNs from humans and mice with Chediak-Higashi syndrome are characterized by reduced degranulatory capacity [20,21], which leads to lower monocyte chemotaxis and chemokine expression [22,23].…”
Section: Pmns Activate Monocytes and Macrophagesmentioning
confidence: 99%
“…In addition, macrophage maturation, migratory capacity, cytokine gene expression and phagocytosis are affected by SGD in both humans and mice [14,15]. In the case of dipeptidyl peptidase I (DPPI) deficiency, which results in a loss of function of the PMN serine proteases elastase, cathepsin G and proteinase-3 [16], a secondary macrophage dysfunction is also observed [17][18][19]. PMNs from humans and mice with Chediak-Higashi syndrome are characterized by reduced degranulatory capacity [20,21], which leads to lower monocyte chemotaxis and chemokine expression [22,23].…”
Section: Pmns Activate Monocytes and Macrophagesmentioning
confidence: 99%
“…Fortunately, recent studies may help understanding these discrepancies. First, Adkison and colleagues (27) have shown that serine protease-deficient neutrophils do not have an intrinsic defect in their ability to transmigrate across the endothelial barrier in response to CXC-like chemokines. Consequently, the inhibition of neutrophil migration evidenced in their study in absence of serine proteases is in keeping with their concept that these proteases modulate the local release and/or processing of cytokines, and possibly of chemokines.…”
Section: Fig 4 Indexes Of Lung Injury At Day 14 After a Repeated Momentioning
confidence: 99%
“…The absence of neutrophil serine proteases prevents induction of collagen-induced arthritis in mice (Adkison et al, 2002). In another study, neutrophil elastase-deficient mice were not susceptible to an antibody-mediated autoimmune dermatosis called bullous pemphigoid disease (Liu et al, 2000).…”
Section: Serine Proteases In Autoimmune Diseasesmentioning
confidence: 98%